Penatalaksanaan fraktur mandibula pada anak dengan cedera kepala sedang - Hadira Hadira; Endang Syamsudin; Bilzardy Ferry Zulkifli (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2016)
Management of mandibular fracture in child with moderate head injury. Mandibular fractures in child with moderate head injuries were relatively rare, the management of child patient need special considerations regarding their age and growth. Management of mandibular fractures in child with moderate head injuries need cooperation with specialists Neurosurgery. This case report aims to explain the management of mandibular fracture in child with moderate head injury. A 7 years old boy ushered to Hasan Sadikin Hospital, with bleeding at head and fracture of the lower jaw. The patient was hit by a motorcycle high speed while crossing the street with unknown mechanism there was history of unconsciousness about 20 minutes, there was bleeding from mouth. GCS 9, asymmetrical face, post suturing in the head and fracture of the lower jaw. Then, examination support, and then diagnosed Moderate Head Injury with Open fractures more than one tabula at right parietal and right mandibular angle fracture, left mandibular parasimphysis fracture. Management according ATLS, with the primary survey, secondary survey and stabilization, then craniectomy debridement. Once a patient is stabilized performed ORIF with regard mandibular growth and development of teeth. craniectomy debridement to prevent the occurrence of intracranial infection because of their open fractures in the bones of the head. Open Reduction and Internal Fixation by installing miniplat with a screw for fixation of mandibular fractures managed to restore the aesthetic and masticatory functions. Open wounds can cause intracranial infections that can develop into meningitis and brain abscess. Management of mandibular fractures in children with head injuries being successful if there is cooperation between specialists Neurosurgery and Oral and Maxillofacial Surgery.